2013
DOI: 10.4055/cios.2013.5.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Total Hip Arthroplasty for Patients with Crowe Type III or IV Developmental Dysplasia of the Hip: Two-Stage Total Hip Arthroplasty Following Skeletal Traction after Soft Tissue Release for Irreducible Hips

Abstract: BackgroundTotal hip arthroplasty (THA) for severe developmental dysplasia of the hip (DDH) is a technically demanding procedure for arthroplasty surgeons, and it is often difficult to reduce the hip joint without soft tissue release due to severe flexion contracture. We performed two-stage THAs in irreducible hips with expected lengthening of the affected limb after THA of over 2.5 cm or with flexion contractures of greater than 30 degrees in order to place the acetabular cup in the true acetabulum and to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Subsequent study has revealed that two-stage THA using interval spacer can improve the Harris Hip Score [22]. In addition, Yoon et al [23] have reported that two-stage THA could reduce the mean leg length discrepancy from 2.95 to 0.8 cm. Furthermore, two-stage THA using debridement or antiloaded spacer implantation can treat effectively for patients with advanced active tuberculosis of the hip and there were no significant differences between the two procedures [9].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent study has revealed that two-stage THA using interval spacer can improve the Harris Hip Score [22]. In addition, Yoon et al [23] have reported that two-stage THA could reduce the mean leg length discrepancy from 2.95 to 0.8 cm. Furthermore, two-stage THA using debridement or antiloaded spacer implantation can treat effectively for patients with advanced active tuberculosis of the hip and there were no significant differences between the two procedures [9].…”
Section: Discussionmentioning
confidence: 98%
“…A potential increased risk of infection remains, owing to the use of an external fixator, and the hospital stay was increased by 2 weeks, corresponding to the time needed for lengthening before the second stage. Yoon et al [22] described a 2-stage operation planned in 6 irreducible hips when expected lengthening of the affected limb after THA was superior to 2.5 cm or when flexion contracture was superior to 30 0 . Surgical hip release with abductor slide, tensor fascia lata, sartorius muscle, iliopsoas tendon, and rectus femoris release was performed through 2 skin incisions during the first stage.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen hips (50%) had a previous surgery on the considered hip, including 6 shelf arthroplasties, 5 intertrochanteric osteotomies, 1 open reduction, and 1 Chiari pelvic osteotomy. The mean follow-up was 16 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) years.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Anlage des Fixateurs kann mit und ohne einen gleichzeitigen Weichteilrelease bzw. eine Kopfresektion erfolgen und auch die Kombination mit einer späteren Verkürzungsos-teotomie ist möglich [33,45,76]. Sogar die primäre Endoprothesenimplantation (in luxierter Position und Kombination mit einem Weichteilrelease sowie Anlage eines Fixateurs externe) mit anschließender Distraktionsbehandlung und final geschlossener Reposition nach erreichtem Längenausgleich ist beschrieben [46].…”
Section: Zweizeitige Prothesenimplantationunclassified